2022
DOI: 10.25110/arqvet.v25i2conv.2022.8037
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade De Híbridos De Milho Pipoca Submetidos a Diferentes Populações Na Semeadura

Abstract: Quando se trata de milho pipoca o Brasil é o segundo maior produtor, mas necessitando ainda de importações para suprir a demanda interna do país, visto a importância de estudos que melhor explorem as recomendações agronômicas para a cultura do milho pipoca. [Revisor1] Assim, o presente estudo objetivou avaliar o impacto da população de plantas sobre algumas variáveis morfológicas e na produtividade final de grãos de dois híbridos de milho pipoca (8203 e 4512). Foram estudadas as populações de 60.000, 65.000, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We did not observe significant effects (p > 0.05) on the interaction between plant density and levels of water depth for any of the traits (Tables 1, 2, and 3), and the ED from the main effects and the interaction between them, in both growing seasons (Tables 1 and 2). These results corroborate the report by Sangiovo et al (2022), who also evaluated commercial hybrids of popcorn plants growing at different densities. They also did not find any differences in ED.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We did not observe significant effects (p > 0.05) on the interaction between plant density and levels of water depth for any of the traits (Tables 1, 2, and 3), and the ED from the main effects and the interaction between them, in both growing seasons (Tables 1 and 2). These results corroborate the report by Sangiovo et al (2022), who also evaluated commercial hybrids of popcorn plants growing at different densities. They also did not find any differences in ED.…”
Section: Resultssupporting
confidence: 91%
“…Many experiments to obtain high crop yields were conducted in Brazil. They investigated plant populations, hybrids, and crop cycles under different levels of management (Silva, Sangoi, Vieira, & Marchesi, 2012;De Souza et al, 2013;Sangiovo et al, 2022). Ávila et al (2011) in their study on popcorn hybrids grown in irrigation depth, observed that the hybrid IAC 125 in the presence of irrigation and in the variation of Kc above the reference for the corn is generally more responsive.…”
Section: Introductionmentioning
confidence: 99%